Graphite: origin, deposits and economics : an exploration study of the Orom Graphite project - Van den Berg, Jacobus Petrus (Rhodes University, Faculty of Science, Department of Geology, 2018)
Developing exploration projects successfully requires that the Reasonable Prospects for Eventual Economic Extraction (RPEEE) be confirmed and based on the global market perception and trend. The exploration methods applied in the attempt to establish this RPEEE must be based on a key management framework that assures the results, and eventually the conclusion, are obtained with best practical and technical approaches whilst managing the risks and capitalizing on each result. The Orom Graphite project is located within the East African Orogenic belt, a suture zone between the Congo craton and the SLAMIN shield, formed during the formation of Gondwana during the late Proterozoic to early-Phanerozoic era. The closing of the Mozambique ocean, and the eventual collision between the craton and shield, occurred along the paleo-earths equator and migrated towards lower latitudes. This, along with the period's biodiversity boom, provided the perfect deposition environment for carbonaceous sediments which were later metamorphosed to amphibolite and granulites grade metamorphism, resulting in the carbonization and the eventual graphitization of these carbonaceous sediments. The project is located within a poorly developed part of Uganda with the closest port situated some 1 500 km to the east in Kenya. The poorly developed infrastructure along with probable high logistical cost assigns a low competitivity index if compared to the economic costs of peer projects. However, the potential resources of the Orom Graphite project suggest that the Life of Mine (LOM) can rival the largest resource currently reported within the market. The current market conditions suggest that a possible oversupply of graphite concentrate will dominate the market within the next 4 to 10 years. This suggests that new graphite projects such as the Orom Graphite project are likely to develop into the production phase once the global supply and demand stabilize. This requires the Orom Graphite project to develop from its current scoping study level to a project development study level associated with a definitive feasibility study. To date, the project developed through mapping, reconnaissance drilling, geophysical survey and trenching programs increasing the Net Present Value (NPV) considerably based upon a Cost-Based Valuation approach using Prospectivity Enhancement Multiplier (PEM). The metallurgical studies could however not produce a graphite concentrate product within industrial grade standards. The risk associated with developing the project further into the Mineral Resource Estimation (MRE) phase was quantified and risk was evaluated by implementing a point decision tree and calculating the Expected Monetary Value (EMV). Due to the unfavourable metallurgical results obtained to date, the risk associated with undertaking an additional metallurgical test is considerable with a slight chance of producing a negative project value estimated at 65%. JP van den Berg Rhodes University Overall, the Orom Graphite project contains favourable geological formations with a potential large resource. Market trends indicate that a considerable resource is currently being developed and can supply the global market for the next 4 to 10 years. The project's location within a landlocked country decreases its economic competitiveness with peer project and the unfavourable, but not conclusive, metallurgical results obtained during the scoping phase do not instil confidence that the project will develop into a productive mine soon. Managing the project development with future graphite demand in mind is the key to determining whether the project still has future value.
Keywords: Graphite; Ore deposits; Geophysics; Graphite mines and mining -- Economic aspects -- Africa, East; Trenches; Project management